2010
DOI: 10.1016/s2255-4971(15)30216-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Enneking Staging System in Relation to Treating Benign Bone Tumors and Tumor-Like Bone Lesions

Abstract: Objective: To evaluate the efficacy of the Enneking staging system for determining the prognosis, planning surgical treatment and indicating adjuvant therapy for benign bone tumors (BBT) and tumor-like bone lesions (TBL). Methods: A retrospective multicenter, descriptive, nonrandomized study was carried out on a representative sample comprising a large series of 165 patients with a total of 168 benign bone tumors and tumor-like bone lesions. The patient sample was typical, and matched the literature in all res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, as a parameter that can only be obtained after surgery, the amount of bleeding is not included in our prediction model. We also found that the Enneking staging was significantly related to the p53 status, which was consistent with previous reports about the role of Enneking staging in planning surgery and adjuvant therapy for bone tumors and tumor-like bone lesions ( 52 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, as a parameter that can only be obtained after surgery, the amount of bleeding is not included in our prediction model. We also found that the Enneking staging was significantly related to the p53 status, which was consistent with previous reports about the role of Enneking staging in planning surgery and adjuvant therapy for bone tumors and tumor-like bone lesions ( 52 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the limbs, intralesional excision is also considered an appropriate choice for stage 3 disease, particularly if local adjuvants such as phenol, hydrogen peroxide, cryosurgery, or polymethyl acrylate are used. 44 , 45 …”
Section: Methodsmentioning
confidence: 99%
“…OS tissues and matched adjacent tissues were collected simultaneously and immediately frozen in liquid nitrogen. The Enneking staging system was used to classify the OS tumors [ 19 ]. The study was approved by the ethics committee of the Second Hospital of Jilin University (2016.169).…”
Section: Methodsmentioning
confidence: 99%